The mediating role of electronic word-of-mouth in the relationship between CSR initiative and consumer satisfaction - Hua, Xiangzhou; Mohd Hasan, Nurul Ain; De Costa, Feroz; Qiao, Weihua (Elsevier, 2024)
The importance of CSR in today's business environment cannot be ignored, especially more and more enterprises realize that when consumers perceive CSR, it will affect consumer behavior and then affect corporate efficiency and reputation. With the widespread application of social media, corporate social responsibility behaviors are easy to be participated and discussed by consumers on the Internet, forming electronic word-of-mouth. Therefore, this paper discusses the influence of electronic word-of-mouth between CSR and consumer satisfaction, taking China's largest Internet enterprise Tencent and its consumers and users as the research object. The overall purpose of this study is to explore the mediating role of electronic word-of-mouth in CSR and consumer satisfaction. This study uses Stimulus-Organism-Response (SOR) theory as the theoretical framework to explain the relationship between CSR initiatives, eWOM and consumer satisfaction. Using the quantitative method of questionnaire survey, taking China's enterprise Tencent as an example, a total of 490 valid questionnaires from Tencent WeChat users from four different levels of cities were received. The PLS-SEM model was used to deeply study the impact of CSR on consumer satisfaction and electronic word-of-mouth. The study found that philanthropic responsibility has a significant impact on consumer satisfaction, but environmental responsibility has no significant impact on satisfaction. At the same time, electronic word-of-mouth plays a key mediating role between the dimension of charitable responsibility and consumer satisfaction, but there is no mediating relationship between the dimension of environmental responsibility and consumer satisfaction. This study is beneficial to other enterprises in the formulation and planning of social responsibility, helps enterprises better understand consumer demands under different CSR dimensions, and provides a useful reference for the formulation of more accurate CSR strategies. © 2024 The Author(s)